Aligning Human Resources and Business Strategy - Holbeche, Linda (Elsevier, 2011)
What difference can an aspiring HR strategist really make to business value? Is HR making the most of its new opportunities to become a pivotal part of the business? In a world where HR can suffer from a low, administrative profile, Linda Holbeche shows how some HR strategists have impressed and delivered at the highest level.